Analisis Pengaruh Ekuitas Merek Dan Harga Terhadap Keputusan Pembelian Serta Pengaruhnya Pada Kepuasan Konsumen Sabun Mandi Shinzui Di Kota Ambon - Pelupessy, Merry Margareth; Christianty, Restia; Tehuayo, Erlinda; Pattiselanno, Grace F. (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to analyze the extent of the influence of Brand Equity and Price on Purchasing Decisions and their Impact on Consumer Satisfaction of Shinzui Bath Soap in Ambon City. This research is a descriptive research. By using questionnaires as a data collection tool as many as 90 respondents. Sampling using purposive sampling. The data analysis method used is Partial least square using smartpls ver 3.0 including validity test and reliability test, as well as hypothesis test and model evaluation test. The results of the analysis show that brand equity is related and influential on purchasing decisions with a t-statistic value of 2,100 because it has a T-statistic value exceeding a value of >1.96, then prices are related and influential on purchasing decisions with a t-statistic value of 8,448 because it has a T-statistic value of less than >1.96 and purchasing decisions are related and affect consumer satisfaction